Direct Effect of the Constitution in the Context of the Modern Constitutional-Legal Though - Manasyan , A. (Bulletin of Yerevan University C: Jurisprudence, 2018)
Issues with regard to the direct effect and direct application of the Constitution are considered in the article. The Author concludes that the content of the mentioned terms, in their essence, differ from each other. In Author’s opinion, effect of the Constitution is the influence that the Basic Law has on the concrete social society from the viewpoint of predetermination and regulation of the social relations, formed within the frames of it. Meanwhile, the application of the Constitution is the state-power activity of competent bodies, implemented in the defined special manner, and aimed at the realization of constitutional norms in a concrete case and adoption of corresponding acts of their application.